Reaction of Some Wheat Varieties to Bipolaris sorokiniana - Laila, L.; Aminuzzaman, F. M.; Islam, M. R.; Islam, M. A. (International Journal of Bio-resource and Stress Management, 2010)
The experiment was conducted at Seed Pathology Laboratory, Sher-e-Bangla Agricultural University, Dhaka, Bangladesh to study the reaction of some wheat varieties to Bipolaris sorokiniana in vitro. The wheat seeds of varieties Sonalika, Kanchan, Barkat, Shatabdi, Aghrani, Pavon-76, Akbar, Gourab, Sourav and Protiva were collected from Bangladesh Agricultural Research Institute (BARI), Gazipur. In blotter test maximum germination (92%) was recorded in the variety Shatabdi, Sourab and Agrani, and minimum (72%) was recorded in Sonalika. Maximum (37%) incidence of seed borne B. sorokiniana was recorded in Sonalika and minimum (12%) in Shatabdi. The highest number of conidia seed-1 (320) was recorded in Sonalika and minimum number (100) was recorded in Shatabdi. Larger Lesion (11.67 mm) was found in Sonalika, Sourav and Kanchan. No lesion (infection) was recorded in Shatabdi, Akbar, Pavon-76 and Protiva where roots were inoculated with B. sorokiniana. Maximum percentage of leaf segment disease (96.67%) was recorded in Sonalika. No lesion was found on the leaf of the variety Shatabdi when the leaves were inoculated with B. sorokiniana in vitro.